2014
DOI: 10.1111/1460-6984.12102
|View full text |Cite
|
Sign up to set email alerts
|

Specific language impairment: a convenient label for whom?

Abstract: Background: The term 'specific language impairment' (SLI), in use since the 1980s, describes children with language impairment whose cognitive skills are within normal limits where there is no identifiable reason for the language impairment. SLI is determined by applying exclusionary criteria, so that it is defined by what it is not rather than by what it is. The recent decision to not include SLI in DSM-5 provoked much debate and concern from researchers and clinicians. Aims: To explore how the term 'specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
191
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(209 citation statements)
references
References 135 publications
6
191
0
12
Order By: Relevance
“…The reasons for the use of SLI as a diagnostic category, both for research and practice, and the limitations of this approach have recently been critically reviewed by Bishop (2014) and Reilly et al (2014b) in a special issue of the International Journal of Language and Communication Disorders, which also included responses from other experts and a joint paper setting out proposals for further developments (Reilly et al, 2014a). Together, these reviews present a substantial critique of the validity and usefulness of SLI as a diagnostic category, supporting the decision to exclude this category from the DSM-5, the latest revision of the Diagnostic and Statistical Manual of Mental Disorders (American Psychiatric Association, 2013); but, see also Rice (2016) for a contrary review supporting the usefulness of SLI as a diagnostic category.…”
Section: Language Impairment As a Risk Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the use of SLI as a diagnostic category, both for research and practice, and the limitations of this approach have recently been critically reviewed by Bishop (2014) and Reilly et al (2014b) in a special issue of the International Journal of Language and Communication Disorders, which also included responses from other experts and a joint paper setting out proposals for further developments (Reilly et al, 2014a). Together, these reviews present a substantial critique of the validity and usefulness of SLI as a diagnostic category, supporting the decision to exclude this category from the DSM-5, the latest revision of the Diagnostic and Statistical Manual of Mental Disorders (American Psychiatric Association, 2013); but, see also Rice (2016) for a contrary review supporting the usefulness of SLI as a diagnostic category.…”
Section: Language Impairment As a Risk Factormentioning
confidence: 99%
“…These criteria include social disadvantage, episodes of otitis media, anomalies of the oral structure and oral motor function, being bilingual, and autism spectrum disorders [ASD: see Bishop (2014)]. Similarly, Reilly et al (2014b) argue for a lack of support for inclusionary criteria of biological (neural and genetic) markers, clinical behavioral markers, and differentiated profiles and outcomes of children with SLI compared to children with non-specific impairments. Furthermore, there is a lack of consistency in the use of different terms for children with language difficulties as used by practitioners and researchers (Dockrell et al, 2006).…”
Section: Language Impairment As a Risk Factormentioning
confidence: 99%
“…In a recent review of specific language impairment, we suggested that eligibility should only be determined once a child's performance has been monitored over time, possibly for a full 12 months. 32 Many if not most of the children who participated in this study would have been ineligible under this stricter criterion.…”
Section: Implications For Clinicians and Policy Makersmentioning
confidence: 99%
“…It has even been suggested that developmental dyslexia and specific language impairment are points on a continuum of learning disorders rather than distinct disabilities (Kamhi & Catts, 1986;cf. Tallal, Allard, Miller, & Curtiss, 1997; but see Bishop & Snowling, 2004;Norbury, 2014;Reilly, Bishop, & Tomblin, 2014).…”
Section: Introductionmentioning
confidence: 99%